Accountable to God alone? : theologising with a hammer : the HIV/AIDS crisis, condoms and Catholicism - Nicholls, Gordon Charles (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2003.